Pengaruh Penggunaan Metode Diskusi dalam Mata Pelajaran PAI Terhadap Minat Belajar Peserta Didik Kelas VIII di SMPIT Al-Ghifari Bojong Gede Bogor - Salsabila Indah Cahyani; Suhendra; Putri Ria Angelina (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to determine whether there is an influence of the use of discussion methods on students' learning interest in PAI subjects in grade VIII SMPIT Al-Ghifari Bojong Gede. The population in this study includes all grade VIII students of SMPIT Al-Ghifari Bojong Gede consisting of 3 classes with a total of 95 students. This study used quantitative methods where the data collection process was carried out by distributing research questionnaires to 95 grade VIII students at SMPIT Al-Ghifari Bojong Gede. The results showed that: (1) the use of discussion method obtained an average of 43.1 results showed that the use of discussion method in PAI subjects was included in the good category. (2) the interest in learning of grade VIII students obtained an average score of 39, this shows that the interest in learning of grade VIII students is included in the category of quite good. (3) the results of a simple linear regression test of 0.000 < 0.05 showed that there was a positive and significant influence of the use of the discussion method on the learning interest of grade VIII students at SMPIT Al-Ghifari Bojong Gede, so that Ha was accepted and Ho was rejected. Therefore, if you want to increase the interest in learning students, one of the things that must be considered is the use of learning methods.